(untitled) (Research, Society and Development, 2020)
According to the statistical notes of the National Institute of Educational Studies and Research Anísio Teixeira (Inep), the number of enrollments for Special Education students increased in 2018 by 33.2% compared to 2014 in Brazil. This article aimed to verify the enrollment rate of Special Education (students from special schools, special classes and included) in Technical Education for Secondary Education in the State of Amapá- Brazil (2015-2018). Methodologically, data were collected on the Inep website and bibliographic research, with an approach that involves mixed methods. In the results, there was an increase in enrollment in the courses integrated in the federal network, while in the concomitant and subsequent courses the rate of increase occurred in the state network. On the other hand, in Youth and Adult Education (EJA), in turn, there was only registration of enrollments in the face-to-face federal network. It is concluded that schools need to be prepared to serve the public of special education, so that they can guarantee an inclusive quality education. For this, greater public investments in education in the north of the country are needed. In addition to national and state commitment, in the development of research that can map the theme of special education in its relation to levels, stages and other teaching modalities (such as EJA), respecting the socioeconomic and cultural differences of the Brazilian regions, as well as its possible educational strengths and weaknesses.